Efficient Pricing and Model Calibration With Large Panels of Options. - Letourneau, Pascal; Stentoft, Lars (Journal of Financial Econometrics, 2025)
We introduce a consistent method for pricing panels of options through time with a single simulation. The approach is particularly useful for pricing options with early exercise features and allows calibrating flexible option pricing models to large panels of such options. We showcase this by calibrating option pricing models with time-varying volatility and asymmetric features to a sample of more than 25,000 American-style options. Our method leverages the homogeneity of option prices, relies only on polynomial approximations using simulated paths, and could be applied to other problems that require estimating optimal stopping times using dynamic programming.